2022
DOI: 10.1038/s41590-022-01215-0
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals evolution of immune landscape during glioblastoma progression

Abstract: Glioblastoma (GBM) is an incurable primary malignant brain cancer hallmarked with a substantial protumorigenic immune component. Knowledge of the GBM immune microenvironment during tumor evolution and standard of care treatments is limited. Using single-cell transcriptomics and flow cytometry, we unveiled large-scale comprehensive longitudinal changes in immune cell composition throughout tumor progression in an epidermal growth factor receptor-driven genetic mouse GBM model. We identified subsets of proinflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(98 citation statements)
references
References 80 publications
8
90
0
Order By: Relevance
“…These polarized BMDMs showed an immunosuppression phenotype that significantly reduces the proliferation and IFNγ production of CD8 + T cells, posing a challenge to developing immunotherapy for GBM. A similar study was recently reported by Yeo et al (48), where the BMDM was observed with an increased proportion at the advanced stage of GBMs. Intriguingly, we found that knocking down ANXA1 significantly decreased the suppression effect of macrophages on CD8 + T cells, and tumor progression in GL261-derived syngeneic glioma mouse models, implying ANXA1 could be a potential target for GBM treatment.…”
Section: Discussionsupporting
confidence: 88%
“…These polarized BMDMs showed an immunosuppression phenotype that significantly reduces the proliferation and IFNγ production of CD8 + T cells, posing a challenge to developing immunotherapy for GBM. A similar study was recently reported by Yeo et al (48), where the BMDM was observed with an increased proportion at the advanced stage of GBMs. Intriguingly, we found that knocking down ANXA1 significantly decreased the suppression effect of macrophages on CD8 + T cells, and tumor progression in GL261-derived syngeneic glioma mouse models, implying ANXA1 could be a potential target for GBM treatment.…”
Section: Discussionsupporting
confidence: 88%
“…This exploration of the TAM population also unveiled a shift from microglia-derived to monocyte-derived TAMs in the TME with tumor recurrence ( 203 ). Notably, high infiltration of monocytic macrophages relative to resident microglia corresponds to increased malignancy in gliomas ( 19 , 204 ). As for the tumor-infiltrating lymphoid population, TCR sequencing of newly diagnosed and recurrent GBMs revealed a diminished TCR repertoire with recurrence ( 22 ), which leads to suppressed T cell-mediated immune response via altered antigen-recognition machinery.…”
Section: Analytical Tools To Explore Gbm Heterogeneitymentioning
confidence: 99%
“…A recent study at the single‐cell level provided new insights into the dynamics of evolution of the immune landscape in the TME in in vivo model systems of GBM, which were confirmed in tumour samples from patients with low‐grade glioma and GBM, respectively. The results identified a large phenotypic heterogeneity at the early stage of GBM development 149 A drastic change in the innate immune cell composition during tumour progression was observed, with a preponderance of proinflammatory (M1‐like) microglia at the early stage followed by infiltration of protumorgenic MDSC (M2‐like) in late‐stage tumours 149 . These data highlight the importance of the immunosuppresive TME and its contribution to GBM immune escape and thus tumour progression.…”
Section: The Immunosuppressive Tumour Microenvironment In Gbmmentioning
confidence: 74%